Isolation and Antibacterial Activity of Mangrove-Derived Streptomyces from the Mandeh Coast, West Sumatra - Fatriza, Ayu Septia; Tjong, Djong Hon; Suliansyah, Irfan; Agustien, Anthoni; Marlina, Marlina; Rusfidra, Rusfidra (Jurnal Biologi Tropis, 2026)
Mangrove ecosystems are recognized as potential environments for microorganisms that produce antibiotics, owing to their distinct environmental features and high levels of microbial rivalry. The objective of this research was to extract and assess the antibacterial properties of Streptomyces species sourced from the mangroves within the Mandeh coastal ecosystem in West Sumatra, Indonesia, targeting specific pathogenic bacteria. Sediment samples were collected from three mangrove locations and processed using serial dilution and spread plate methods on International Streptomyces Project 2 (ISP-2) media. Data were analyzed descriptively based on the size of the inhibition zone formed against the tested bacteria. The results showed Streptomyces-like characteristics characterized by colony morphology and Gram staining. Antibacterial activity was evaluated using a disc diffusion test against methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli ATCC 25922, and Cutibacterium acnes. A total of seventeen isolates exhibiting typical Streptomyces characteristics were obtained. The antibacterial test showed varying inhibitory activity among the isolates against the tested pathogens. The STMMI isolate showed the strongest inhibition against MRSA with an inhibition zone of 23.61 ± 0.62 mm and also showed considerable activity against C. acnes (16.64 ± 1.12 mm). Meanwhile, the STMML isolate showed the highest inhibition against E. coli ATCC 25922 with an inhibition zone of 17.06 ± 0.63 mm. Some isolates showed broad-spectrum antibacterial activity, while others showed selective inhibition against certain pathogens. In conclusion, mangrove sediments from the Mandeh coastal ecosystem harbor a variety of Streptomyces with promising antibacterial potential. This study highlights the importance of Indonesian mangrove ecosystems as a potential reservoir of bioactive microorganisms for future antibiotic discovery.